2021
DOI: 10.1002/cti2.1300
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33/ST2 axis deficiency exacerbates neutrophil‐dominant allergic airway inflammation

Abstract: Objective The IL‐33/ST2 axis has been extensively investigated in type 2 eosinophilic inflammation. Here, we aimed to investigate the role of the IL‐33/ST2 axis in neutrophil‐dominant allergic airway inflammation. Methods House‐dust mite (HDM) extract and lipopolysaccharide (LPS) were administered to establish a murine model of neutrophil‐dominant allergic airway inflammation. The formation of neutrophilic extracellular traps (NETs) in the lung tissues was demonstrated by immunofluorescence imaging. Mature IL‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Furthermore, our results revealed that the SPA4 peptide restores the LPS-disrupted TEER by mainly affecting the subcellular distribution of tight junction proteins (Figure 3). Similarly, changes in localization pattern, but no effect on expression levels of occludin, have been reported earlier in human bronchial epithelial cells challenged with E. coli O111:B4-derived LPS, pollutants, and cigarette smoke, through hyperphosphorylation of occludin (Cao et al, 2015;Ma et al, 2021). Similarly, tyrosine phosphorylation of ZO-1, occludin, and E-Cadherin results in their re-distribution at a cellular level (Samak et al, 2014).…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, our results revealed that the SPA4 peptide restores the LPS-disrupted TEER by mainly affecting the subcellular distribution of tight junction proteins (Figure 3). Similarly, changes in localization pattern, but no effect on expression levels of occludin, have been reported earlier in human bronchial epithelial cells challenged with E. coli O111:B4-derived LPS, pollutants, and cigarette smoke, through hyperphosphorylation of occludin (Cao et al, 2015;Ma et al, 2021). Similarly, tyrosine phosphorylation of ZO-1, occludin, and E-Cadherin results in their re-distribution at a cellular level (Samak et al, 2014).…”
Section: Discussionsupporting
confidence: 69%
“…The effect of TNF-α stimulation was inhibited by subsequent addition of MMP9 inhibitors (SB-3CT or MMP9-IN-I) or silvestrol ( Figure 5H and Supplementary Figure 6F and -G ). 46 , 47 As a positive control, HEI-193 cells invaded through collagen-I with recombinant MMP9, an effect that was inhibited with MMP inhibitors and silvestrol ( Figure 5J ). Similar results were observed in MD-MSCs ( Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The present asthma model was developed according to previous methods. 19 20 Briefly, mice were sensitized intranasally (i.n.) using HDM (25 μg/mouse, cat# XPB82D3A25; Greer, London, USA) with or without LPS (10 μg/mouse, E. coli serotype O111: B5, cat# L2880, Sigma-Aldrich, St. Louis, MO, USA) dissolved in 20 μL of PBS once daily on days 0, 1, and 2; then, challenged with HDM (25 μg/mouse) alone i.n.…”
Section: Methodsmentioning
confidence: 99%